Hip adductor muscle function in forward skating - Chang, R.; Turcotte, R.; Pearsall, D. (Sports Biomechanics, 2009)
Adductor strain injuries are prevalent in ice hockey. It has long been speculated that adductor muscular strains may be caused by repeated eccentric contractions which decelerate the leg during a stride. The purpose of this study was to investigate the relationship of skating speed with muscle activity and lower limb kinematics, with a particular focus on the role of the hip adductors. Seven collegiate ice hockey players consented to participate. Surface electromyography (EMG) and kinematics of the lower extremities were measured at three skating velocities 3.33 m/s (slow), 5.00 m/s (medium) and 6.66 m/s (fast). The adductor magnus muscle exhibited disproportionately larger increases in peak muscle activation and significantly prolonged activation with increased speed. Stride rate and stride length also increased significantly with skating velocity, in contrast, hip, knee and ankle total ranges of motion did not. To accommodate for the increased stride rate with higher skating speeds, the rate of hip abduction increased significantly in concert with activations of adductor magnus indicating a substantial eccentric contraction. In conclusion, these findings highlight the functional importance of the adductor muscle group and hip abduction-adduction in skating performance as well as indirectly support the notion that groin strain injury potential increases with skating speed.